2019
DOI: 10.1080/09638288.2019.1573383
|View full text |Cite
|
Sign up to set email alerts
|

Documentation of everyday life and health care following gastrostomy tube placement in children: a content analysis of medical records.

Abstract: Background: Everyday routines play a vital role in child functioning and development. This study explored health professionals' documentation of everyday life and health care during the first year following gastrostomy tube placement in children and the content of intervention goals. Methods: The medical records of 39 children (median age 38 months, min-max: 15-192) in one region of Sweden were analysed. A content analysis approach was used with an inductive qualitative analysis supplemented by a deductive, qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…But despite the fact that the child’s feeding difficulties had marked both the former and present family life, parents expressed a lack of interest in health care professionals to gain an understanding or provide support beyond the practical handling of the G-tube or the nutritional intake of the child. The importance of a more multidimensional approach health care has been put forward by Craig (2013) and Backman et al (2020) as well as in the assessment framework suggested by Brotherton et al (2007) . The findings from this study expand upon previous research by focusing on the ecocultural context of the child.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But despite the fact that the child’s feeding difficulties had marked both the former and present family life, parents expressed a lack of interest in health care professionals to gain an understanding or provide support beyond the practical handling of the G-tube or the nutritional intake of the child. The importance of a more multidimensional approach health care has been put forward by Craig (2013) and Backman et al (2020) as well as in the assessment framework suggested by Brotherton et al (2007) . The findings from this study expand upon previous research by focusing on the ecocultural context of the child.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the young adults, the parents reported reduced pressure at mealtimes and satisfaction with their child’s feeding regimen, but also a feeling of being forced to accept the G-tube insertion, problems with supportive childcare, and restricted ability for the parents to leave the home. Other daily parental challenges associated with pediatric G-tube feeding include practical limitations related to carrying and sterilizing equipment ( Craig & Scambler, 2006 ), dilemmas relating to maintaining participation in everyday activities, managing responses to the use of tubes for feeding and doing what feels right for their child ( Edwards & Leafman, 2019 ; Hopwood et al, 2020 ), caregiver burden handling health care contacts ( Backman et al, 2020 ), and behavioral problems in children ( Burklow et al, 2002 ). Russel et al (2017) explored the family mealtime routines of six families of children with cerebral palsy who required G-tube feeding.…”
mentioning
confidence: 99%
“…The EHR is one of the main tools for multi-professional cooperation and communication with patients. Furthermore, the EHR should be appreciated as an agent, playing an active and constitutive role in setting objectives, planning, documenting delivery of care and assessing outcomes [ 16 ]. The content of the EHR is important as it serves professionals in making decisions and documenting the deliberations which have been made and the care that has been given [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…These comprise resources and ecological fit in a particular cultural context, an activity's value for the family, the balance of competing interests and conflicts among family members, accommodations as well as the predictability and stability of an activity (Weisner, 2002;Weisner et al, 2005). Ecocultural theory was chosen as the theoretical framework, as it has been proven valuable when exploring young children's experiences of prior-to-school care (Grace and Bowes, 2011) and understanding accommodation to sustainable everyday routines in families in which a child uses a G-tube as documented by healthcare professionals (Backman et al, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%